The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4943238
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal linear stability analysis of stratified planar wakes: Velocity and density asymmetry effects

Abstract: Right click to open a feedback form in a new tab to let us know how this document benefits you.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…Several distinct flame modes of symmetric and asymmetric vortex shedding were observed as inflow velocity approaches blow-off limit in the overall laminar flow range. It was found that the flame modes were noticeably changed due to the enhanced fluid dynamic effects of density ratio, consistent with the observations from earlier experimental studies [5,[13][14][15][16]. The fluid dynamic effects were found to be an important factor in determining the ultimate blow-off limit, and the mode was properly described by the Strouhal number scaling.…”
Section: Introductionsupporting
confidence: 86%
“…Several distinct flame modes of symmetric and asymmetric vortex shedding were observed as inflow velocity approaches blow-off limit in the overall laminar flow range. It was found that the flame modes were noticeably changed due to the enhanced fluid dynamic effects of density ratio, consistent with the observations from earlier experimental studies [5,[13][14][15][16]. The fluid dynamic effects were found to be an important factor in determining the ultimate blow-off limit, and the mode was properly described by the Strouhal number scaling.…”
Section: Introductionsupporting
confidence: 86%
“…In terms of propulsion, there are advanced technologies like ultra-high bypass ratio turbofan engines, hybrid-electric and full-electric concepts [12]. The future aircraft engines will have cleaner/lowemissions and improved combustors [13], [14]. Such combustors will control combustion instabilities, a phenomenon observed in present-day aircraft combustors [13], [14].…”
Section: Future Aviation Technologiesmentioning
confidence: 99%
“…The future aircraft engines will have cleaner/lowemissions and improved combustors [13], [14]. Such combustors will control combustion instabilities, a phenomenon observed in present-day aircraft combustors [13], [14]. These next generation of improved combustors further increase the safety aspect of an aircraft [13], [14].…”
Section: Future Aviation Technologiesmentioning
confidence: 99%
See 1 more Smart Citation